Kinetics of the natural, humoral immune response to Salmonella enterica serovar Typhi in Kathmandu, Nepal. - Pulickal, A; Gautam, S; Clutterbuck, E; Thorson, S; Basynat, B; Adhikari, N; Makepeace, K; Rijpkema, S; Borrow, R; Farrar, J; Pollard, A (2009)
Typhoid fever is a major public health problem in developing countries, conservatively estimated to occur in 17 million cases and be responsible for 200,000 deaths annually. We investigated the acquisition of natural immunity to Salmonella enterica serovar Typhi in a region where typhoid is endemic by testing sera from an age-stratified sample of 210 healthy participants in Kathmandu, Nepal, for bactericidal activity toward S. Typhi and for anti-Vi capsular polysaccharide antibodies. Bactericidal titers in children were significantly lower than those in newborns and adults (P < 0.0001). Anti-S. Typhi bactericidal geometric mean titers were age dependent, increasing 10-fold during childhood. Anti-Vi polysaccharide antibody geometric mean concentrations were also lower in children than in adults. Data presented here indicate the possibility of a relationship between low levels of bactericidal activity toward S. Typhi in serum and susceptibility to disease, as observed for other polysaccharide-encapsulated bacteria. Bactericidal antibody may be a marker of protective immunity against S. Typhi.